(untitled) (Malay Literature, 2021)
In Malay culture, the concept of air tangan ibu (mother’s handiwork) generally refers to the noble effort of a woman in cooking dishes for her children. Philosophically, however, air tangan ibu does not merely refer to a mother’s cooking but encompasses the love, earnestness and sincerity of the mother in preparing dishes for her children. It is this emotion that flows through it that will lead a child to remember its mother and her sacrifices. In fact, in the context of Islam, the philosophy of air tangan ibu is in line with the encouragement of the Rasulullah s.a.w. that everyone on this Earth should give their best in their everyday occupation. Therefore, this study analyses selected Malay short stories that display their writer’s creativity through the dishes highlighted in each of these works. The study unravels the concept of "air tangan ibu" as a backbone of education, as a reminder, and as a character-shaping force, based on the short stories "Kerana Kuih Koci" (Fathul Khair Mohd Dahlan), "Bihun Goreng Berkuah Laksa" (Nordin Saad) and "Serondeng Nasi Pulut" (Jamilah Epin). The study makes clear that air tangan ibu in Malay culture highlights the ability of writers to showcase the culinary creativity of the Malays in each of these short stories, which ultimately has a universal meaning to people in their lives the world over. Keywords: Air tangan ibu, Malay culinary culture, selected Malay short stories